In vitro study on the efficacy of plastic wraps used as surface barriers on clinical contact surfaces Pilot study - De Vera, Jamie Evon O.; Del Castillo, Suchelle Ann B.; Escoto, Elmer Jesus T (Co-author).; Rosanes, Rose Anne Q. (Adviser).
In the dental profession, practice of infection control is one of the key elements in looking after the welfare of both dental healthcare personnel and patients. The Centers for Disease Control and Prevention (CDC) includes the usage of surface barriers such as plastic wraps on clinical contact surfaces so as to prevent the spread of infection, especially through direct contact between the dental practitioner, the patient, and the dental equipment.OBJECTIVE: The study was done to determine the efficacy of locally available surface barriers - commercially available plastic wraps and disposable plastic sleeves - used on clinical contact surfaces. METHODOLOGY: Laboratory experiments in which ml 3x10 CFU/ml Staphylococcus aureus suspension were inoculated on surface barrier samples placed on blood agar plates and on plates not covered with surface barriers. After an exposure time of 1 hour, the plates were incubated and bacterial counts were done after 24 and 48 hours of incubation. RESULTS: Results showed that bacterial colonies were still present on plates covered with surface barriers but of fewer number compared to the plates not covered with surface barriers. Higher number of bacterial colonies were also found on the plate covered with deformed surface barriers compared to those that were intact. Using the Kruskal Wallis test, the computed p value of 0.007 was less than α=0.05. CONCLUSION: Based on the results, it can therefore be concluded that there is a significant difference in the number of bacterial between surfaces without surface barriers compared with those with surface barriers. Maintaining the integrity of the plastic wrap is also essential for its efficacy.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.